2013
DOI: 10.5847/wjem.j.issn.1920-8642.2013.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Effect of metoprolol on myocardial apoptosis after coronary microembolization in rats

Abstract: BACKGROUND:Coronary microembolization (CME) is a serious complication following percutaneous coronary intervention (PCI) in patients with acute coronary syndromes. The use of metoprolol before PCI can significantly protect ischemic myocardium from myocardial damage, but the function of metoprolol in the treatment of CME is not entirely clear. This study was to explore the effect and significance of metoprolol on myocardial apoptosis and caspase-3 activation after CME in rats.METHODS:Thirty rats were randomly d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 22 publications
1
20
0
Order By: Relevance
“…All β-blockers are known to inhibit cardiomyocyte apoptosis [ 7 10 ]. However, changes in CI over time in response to treatment with different β-blockers were not similar.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All β-blockers are known to inhibit cardiomyocyte apoptosis [ 7 10 ]. However, changes in CI over time in response to treatment with different β-blockers were not similar.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that β-blockers are effective in mitigating cardiomyocyte apoptosis and they are the standard of care to reduce infarct size after cardiac ischemia. Aten and Met are 2 nd generation cardioselective β-blockers that reduce cardiomyocyte apoptosis caused by conditions such as coronary microembolization and exposure to lipopolysaccharides (LPS) [ 7 , 8 ]. Car and Neb are 3 rd generation β-blockers with additional vasodilative effects [ 9 , 10 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Five fields were randomly selected in each HBFP staining (×100), and infarction area was quantified by 2D deconvolution algorithm using the Leica QWin imaging software (Leica Company) and demonstrated as the average percentage of the total area of the section analyzed. 24 The relative ischemic area was calculated as follows: ischemic area/total area × 100%.…”
Section: Tissue Collection and Sample Processingmentioning
confidence: 99%
“…All three measurements represented the averages of three cardiac cycles. 10 Echocardiographic examination was performed by an experienced echocardiography specialist.…”
Section: Cardiac Function Evaluationmentioning
confidence: 99%